Highly Sensitive Detection of Malathion Based on FRET between Au/Fe3O4 and Rhodamine B. (5th July 2019) - Jia, Di; Ma, Dongqing; Du, Xiaodong; An, Lijuan
Abstract : In this paper, Au/Fe3 O4 nanoparticles (Au/Fe3 O4 NPs) were prepared and a method for detecting malathion was constructed based on fluorescence resonance energy transfer (FRET) between Au/Fe3 O4 NPs and Rhodamine B (RhB). RhB could be electrostatically adsorbed to the surface of Au/Fe3 O4 NPs resulting in a low fluorescent background. The malathion hydrolysate with ‐SH can compete with RhB to form a stronger Au─S bond, thereby promoting the desorption of RhB from the surface of Au/Fe3 O4 NPs. This process causes the fluorescence emission to recover. The result demonstrated that fluorescence quenching efficiency of Au/Fe3 O4 could reach 50% at 579 nm and the fluorescence recovery efficiency of malathion hydrolysate could reach 61% at 579 nm. The limit of detection (LOD) of malathion was as low as 0.59 μM. The linear range of detection was 27.24–99.89 μM. Au/Fe3 O4 NPs could be reused by a magnetic concentration‐washing process. Abstract : Schematic illutration for the detection of malathion based on FRET between the Au/Fe3 O4 NPs and RhB.